Pneumothorax Spontan pada Pasien Penyakit Paru Obstruktif Kronis - Davidtuan Andartua Sihombing (PT Dexa Medica, 2023)
Secondary spontaneous pneumothorax occurs due to underlying lung disease. Chronic obstructive pulmonary disease is the most common cause of secondary spontaneous pneumothorax. Secondary spontaneous pneumothorax can develop into a life-threatening tension pneumothorax. In this case, a 63-year-old man came with chief complaint of severe shortness of breath. The patient has a history of chronic obstructive pulmonary disease. Chest X-ray identified a pneumothorax on the right side. Then the needle decompression was immediately performed due to suspected tension pneumothorax. After needle decompression, shortness of breath was relieved, and then the patient was planned for water seal drainage insertion in the intensive care unit.